Investigation of tablet disintegration pathways by the combined use of magnetic resonance imaging, texture analysis and static light scattering - Dvořák, Jakub; Tomas, Jan; Lizoňová, Denisa; Schöngut, Marek; Dammer, Ondřej; Pekárek, Tomáš; Beránek, Josef; Štěpánek, František (International journal of pharmaceutics, 2020)
Efficient tablet disintegration is a pre-requisite for fast and complete drug dissolution from immediate release formulations. While the overall tablet disintegration time is a routinely measured quality attribute of pharmaceutical products, little attention is usually paid to the analysis of disintegration fragments and the cascade of elementary steps that lead to their formation. In this work, we investigate the disintegration pathways of directly compressed tablets by a unique combination of three methods: (i) magnetic resonance imaging (MRI), to gain insight into structural changes of tablets during disintegration; (ii) texture analysis, to measure the disintegration kinetics; and (iii) static light scattering, to characterise the size distribution of disintegration fragments. By systematically varying the tablet composition (50-90% of ibuprofen as a model active ingredient, 0-4% of croscarmellose sodium disintegrant, 6-50% of lactose monohydrate filler), a relationship between the tablet formulation, the size distribution of the disintegration fragments and the dissolution rate of the active ingredient has been established. To interpret the experimental observations, we analyse the disintegration fragments by Raman mapping and relate their composition and structure to the micro-scale arrangement of individual formulation components inside the tablet.
Keywords: farmaceutická chemie; magnetická rezonanční tomografie; Tablets; tablety; Wetting; Magnetic Resonance Imaging; pomocné látky; Particle size distribution; Solubility; Excipients; Disintegration; Dissolution; rozpustnost; Chemistry, Pharmaceutical; Direct compression